Effect of nitrogen fertilization on central tendency and spatial heterogeneity of soil moisture, pH and dissolved organic carbon and nitrogen in two bioenergy croplands. Issue 3 (10th March 2022) - Wang, Xuehan; Jian, Siyang; Gamage, Lahiru; Li, Jianwei
Abstract: Background: Soil moisture, pH, dissolved organic carbon and nitrogen (DOC, DON) are important soil biogeochemical properties in switchgrass (SG) and gamagrass (GG) croplands. Yet their spatiotemporal patterns under nitrogen (N) fertilization have not been studied. Aims: The objective of this study is to investigate the main and interactive effects of N fertilization and bioenergy crop type on central tendencies and spatial heterogeneity of soil moisture, pH, DOC and DON. Methods: Based on a 3‐year long fertilization experiment in Middle Tennessee, USA, 288 samples of top horizon soils (0–15 cm) under three fertilization treatments in SG and GG croplands were collected. The fertilization treatments were no N input (NN), low N input (LN: 84 kg N ha −1 in urea) and high N input (HN: 168 kg N ha −1 in urea). Soil moisture, pH, DOC and DON were quantified. And their within‐plot variations and spatial distributions were achieved via descriptive and geostatistical methods. Results: Relative to NN, LN significantly increased DOC content in SG cropland. LN also elevated within‐plot spatial heterogeneity of soil moisture, pH, DOC and DON in both croplands though GG showed more evident spatial heterogeneity than SG. Despite the pronounced patterns described above, great plot to plot variations were also revealed in each treatment. Conclusion: This study informs the generally low sensitivity of spatiotemporal responses in soil biogeochemical features to fertilizer amendments in bioenergy croplands. However, the significantly positive responses of DOC under low fertilizer input informed the best practice of optimizing agricultural nutrient amendment.